Assessment of subclinical left ventricular dysfunction with speckle-tracking echocardiography in hyperthyroid and euthyroid Graves' disease and its correlation with serum TIMP-1. Issue 2 (4th March 2021) - Duzen, Irfan Veysel; Tabur, Suzan; Ozturk, Sadettin; Savcilioglu, Mert Deniz; Alıc, Enes; Yetisen, Mustafa; Sanli, Sıddık; Goksuluk, Huseyin; Vuruskan, Ertan; Altunbas, Gokhan; Coskun, Fatma Yılmaz; Kaplan, Mehmet; et al.
Abstract: Background: Graves' disease has a multitude of effects on the cardiovascular system. In the detection of subclinical left ventricular dysfunction, speckle-tracking echocardiography is more useful than conventional echocardiography. The aim of the present study was to compare the longitudinal global strain values and venous blood concentration of (tissue inhibitor of metalloproteinase-1) TIMP-1, a regulator of the extracellular matrix, among hyperthyroid patients with Graves' disease, euthyroid patients with Graves' disease and healthy control subjects. Materials and methods: The study enrolled 40 hyperthyroid patients with newly diagnosed Graves' disease, 40 patients with Graves' disease who were euthyroid for at least 6 months and 40 control subjects with normal thyroid function. Participants underwent conventional echocardiography and speckle-tracking echocardiography to obtain segmental and global longitudinal strain values. In addition, the serum TIMP-1 value was assessed in the venous blood samples of the participants. Results: The hyperthyroid Graves' patients showed greater serum TIMP-1 levels versus the control group and the euthyroid Graves' group. Compared to the control group, the TIMP-1 level was also significantly higher in the euthyroid Graves' group. Lower GLS (global longitudinal strain) average and GLS2C, GLS3C, GLS4C values were observed in both the hyperthyroid and euthyroid Graves' patients compared to the control group. The euthyroid Graves' patients and hyperthyroid Graves' patients had similar GLS values. The serum TIMP-1 level was negatively correlated with global strain values. Conclusion: Graves' disease coexists with impaired segmental and global longitudinal strain and increased TIMP-1 levels. This coexistence seems to be independent of serum thyroid hormone levels.